2021
DOI: 10.5223/pghn.2021.24.3.273
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic-Assisted Percutaneous Endoscopic Gastrostomy Reduces Major Complications in High-Risk Pediatric Patients

Abstract: Purpose Percutaneous endoscopic gastrostomy (PEG) is a safe method to feed patients with feeding difficulty. This study aimed to compare the outcomes of conventional PEG and laparoscopic-assisted PEG (L-PEG) placement in high-risk pediatric patients. Methods In our tertiary pediatric department, 90 PEG insertions were performed between 2014 and 2019. Children with severe thoracoabdominal deformity (TAD), previous abdominal surgery, ventriculoperitoneal (VP) shunt, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…This has been reported in previous studies, although some authors argue for different preferable operative techniques. 4,5,[16][17][18] The most common reason to receive a gastrostomy in our study was an underlying neurological disease. Comparing with mentioned group of patients, we could see that the oncologic patients reported lower incidence of granulomas, more postoperative pain and a higher rate of infections.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This has been reported in previous studies, although some authors argue for different preferable operative techniques. 4,5,[16][17][18] The most common reason to receive a gastrostomy in our study was an underlying neurological disease. Comparing with mentioned group of patients, we could see that the oncologic patients reported lower incidence of granulomas, more postoperative pain and a higher rate of infections.…”
Section: Discussionmentioning
confidence: 77%
“…Our study supports the idea that the technique should be chosen according to the surgeons' experience and suitability for the patient. This has been reported in previous studies, although some authors argue for different preferable operative techniques 4,5,16–18 …”
Section: Discussionmentioning
confidence: 99%
“…Such complications encompassed severe outcomes like death, peritonitis, visceral injury, ileus, and the need for repeat surgery (18). The most minor complications after PEG include wound discharge, leakage, and hyperemia (5,19,20). It is our belief that the variation in reported rates of minor complications can be attributed to variations in data collection and reporting practices across different centers.…”
Section: Discussionmentioning
confidence: 99%
“…However, fundoplication or gastrostomy using laparoscopy cannot shorten the procedure time or eliminate the need for general anesthesia, although a recent study reported that laparoscopic PEG may be safer than conventional PEG in high-risk pediatric patients with severe thoracoabdominal deformity, previous abdominal surgery, ventriculoperitoneal shunt, and abdominal tumors. 14 15 In addition, the difference in the procedures time depends more on the ability of the operator than on the procedure method. In this study, among the cases in which gastrostomy was performed again, there was a case in which the stormy site was placed too close to the pylorus, causing ballooning to interfere with gastric emptying.…”
Section: Discussionmentioning
confidence: 99%